(3GdHOGjI hGdfgGjIs - (3ESeGYjd Hf YeQ Hf cKjQ Hf Vqh Hf OQY GdbQTj GdHUQhj Ke GdOeTbqj, CHh GdaOGA, YeGO GdOjf,J (B774 (3g` s ((3Ydi Hf jhSa Hf CMeO Hf YHO GdgGOi s)
(3ChdgG (B:s
(3ESdGe YeQh Hf GdYGU hNGdO Hf GdhdjO s
(3BNQgG (B:s
(3HGf OdGFd GdfHhI s
(3fSNI KGfjI ef GdLRA GdQGHYs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B320 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B283s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B49 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B43 s
Keywords: (3GdJGQjNs